2018
DOI: 10.13102/sociobiology.v65i3.2880
|View full text |Cite
|
Sign up to set email alerts
|

Density and Spatial Distribution of Nests of Ectatomma ruidum and Pheidole fallax (Hymenoptera: Formicidae), as Response to the Recovery of Coal Mine Areas

Abstract: In this study, the spatial pattern of two ant species of different feeding habits, Ectatomma ruidum and Pheidole fallax (Hymenoptera: Formicidae) was assessed in rehabilitated areas of “Cerrejón” coal mine (Colombia). We tested whether there is a relationship between spatial distribution pattern, age rehabilitation and temporal changes. Three sites with different ages of rehabilitation (1, 9 and 20 years) and a secondary forest were sampled during dry and rainy seasons. Within four plots (6 x 40m) per site, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Another possible explanation could be related to the size of the colony, although this was not evaluated. The high rate of soil turnover found in the study area [25] could explain why nests do not reach larger sizes. Some generalist ant species have been documented to not have a specific construction pattern, which would coincide with P. fallax presenting irregular patterns in the architecture of its nests, unlike fungus-eating ants, which build more elaborate and deeper nests than detritus-/seed-collecting ants [46].…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Another possible explanation could be related to the size of the colony, although this was not evaluated. The high rate of soil turnover found in the study area [25] could explain why nests do not reach larger sizes. Some generalist ant species have been documented to not have a specific construction pattern, which would coincide with P. fallax presenting irregular patterns in the architecture of its nests, unlike fungus-eating ants, which build more elaborate and deeper nests than detritus-/seed-collecting ants [46].…”
Section: Discussionmentioning
confidence: 90%
“…It is important to highlight that the four additional years at the 20-year-old site are not the reason for the greater supply of resources. Maybe this difference is more related to better habitat conditions at the 20-year-old site, which promote the establishment of a greater number of nests both for this species [15,25] and for others [14,34]. Furthermore, species of the Pheidole genus have small foraging areas (±7 m) [35], which would indicate that the resources collected are close to where the nests are located.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ectatomma ruidum and Pheidole fallax) could be contributing in seed dispersal and re-establishment of vegetation in these areas [33]. Another study on sites with different ages of rehabilitation from coal mining found that the nest density of ant Pheidole fallax ranged increases with the rehabilitation age of the sites [34]. A study on clear cut logging of timer trees in USA found that ant species assemblages respond to alteration of habitats where the populations of the invasive ant Solenopsis invicta and Pheidole species increased while the populations of the native ant species are significantly fell [35].…”
Section: Ants As Indicators Of Restorationmentioning
confidence: 99%